ANALISIS KESEGARAN JASMANI INDEKS MASSA TUBUH (IMT) DAN DAYA TAHAN KARDIOVASKULAR PEMAIN BOLAVOLI SPARTA UNIVERSITAS NEGERI MAKASSAR - Sarifin G; A. Ulfiana Fitri; Rahmad Risan (Program Studi Ilmu Keolahragaan, 2022)
This study aims to obtain answers to the problem: is there a relationship between the level of physical fitness. body mass index (BMI) and cardiovascular endurance of Sparta volleyball players. Makassar State University. This research is descriptive. Population and sample are volleyball players from Sparta UNM. selected by random sampling. obtained a sample of 10 people. The data analysis technique used was correlational test using computer facilities through the SPSS 16 program. Based on the results of data analysis showed that the level of physical fitness. body mass index (BMI) and cardiovascular endurance of Spartan volleyball players. Makassar State University with a total of 10 with the results of physical fitness analysis. namely 5 people who fall into the good criteria with a percentage of 50%. and 5 people who fall into the moderate criteria with a percentage of 50%. the second test body mass index is 7 people who fall into the ideal criteria with a percentage of 70%. and 3 people who fall into the overwight criteria with a percentage of 30%. and the third test of cardiovascular endurance. namely 3 people who fall into the criteria Enough with a percentage of 30%. 3 people who fall into the criteria of less with a percentage of 30%. 1 person who falls into good criteria with a percentage of 10%. and 3 people who fit the criteria very well with a percentage of 30%.